PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 11 SEMUNAI KECAMATAN PINGGIR KABUPATEN BENGKALIS - ', Zanimar; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low yield learning science students, with an average value of 62.20, therefore, the researchers provide an alternative implementation of cooperative learning model Teams Student Achievement Division (STAD) in the fourth grade SDN 11 Semunai . This study aims to improve learning outcomes IPA fourth grade students of SD Negeri 11 Semunai for Implementation Model Cooperative Learning Teams type Student Achievement Division (STAD). Design research is action research (PTK) with two cycles. Based on the analysis of research data after applying cooperative learning model Student Team Achievement Division (STAD), the average percentage of teachers in the first cycle of activity increased 70.83% to 85.41% in the second cycle. The average percentage of student activity also increased, namely 62.5% in the first cycle increased to 80.74% in the second cycle. student learning outcomes in basic score with the average value of 62.2 and the first cycle increased with an average value of 71.0 class with an increasing percentage of learning outcomes 13.61% and the percentage of students who complete 68%, and the second cycle increased again by average 83.2 -rata class with an increasing percentage of learning outcomes 13:46% and the percentage of students who complete 84%. These results show that the implementation of cooperative learning model Student Team Achievement Division (STAD) .Can improve learning outcomes IPA fourth grade students of SD Negeri 11 Semunai Uptown BengkalisÂ Key Words: Â Student Teams Achievement Division, learning outcomes IPA